Mitigasi Longsor Dengan Penataan dan Peningkatan Kemampuan Kawasan Perbukitan Pada by Pass BIL-MANDALIKA Sebagai Infrastruktur Penunjang Kawasan Ekonomi Khusus (KEK) Mandalika Lombok : Landslide Mitigation by Structuring and Increasing the Capability of Hill Areas on By Pass BIL-MANDALIKA as Supporting Infrastructure for The KEK Mandalika, Lombo - Fahrudin Fahrudin; Mahrup Mahrup; IGM Kusnarta; Padusung Padusung; I Nym Soemeinaboedhy (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2023)
One of the tourist destinations in Lombok, West Nusa Tenggara is the Special Economic Zone Mandalika (KEK Mandalika), a coastal tourism area with various supporting infrastructures on an international scale covering an area of 1,035.67 hectares. The pace of development brings environmental impacts, especially the morphology of the land in the form of mountains and hills is exposed by the conversion of land functions from proteced forest to agricultural areas without the application of land conservation methods. Bypass BIL-KEK Mandalika as the main connecting road for this tourism area is 17.2 km long flanked by hills with a slope of >30o and almost all hilly areas have been converted into agricultural areas. In this area there is minimal standing vegetation accompanied by unstable physical conditions, making all hilly areas on the BIL-KEK Madalika bypass classified as a Very High Erosion Hazard Level which reaches > 560 tons/ha/year which triggers more potential hazards. big like landslides and floods. Various steps have been taken, such as: 1) Integration of porang (Amorphopallus) and standing vegetation (canopy) applied in hilly areas in the Bypass BIL-KEK Mandalika area; 2) Emphasizing and preventing the conversion of buffer zones; 3) Rehabilitation of the Bypass BIL-KEK Mandalika Hills Area.